Preparation and application of L-cysteine modified island-shaped cobalt sulfide-cobalt oxide heterogeneous nanosheet array / carbon paper material

By designing an island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array on carbon paper, the high cost, time-consuming and complex sample preparation of Trp enantiomers in the prior art is solved, and the excellent recognition and detection capabilities of Trp enantiomers are achieved.

CN119688801APending Publication Date: 2025-03-25HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411802690.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, long time and complex sample preparation in Trp enantiomer chiral recognition and quantitative detection, and poor conductivity of metal organic frameworks (MOFs) limits the electrochemical detection performance.

Method used

L-cysteine ​​modified island-shaped cobalt sulfide-cobalt oxide heterogeneous nanosheet array/carbon paper is used as the electrochemical chiral sensor electrode material. Through the synergistic action of the island-shaped heterostructure and L-cysteine, the electrochemical performance and chiral recognition capabilities are improved.

Benefits of technology

It realizes excellent recognition and detection capabilities of Trp enantiomers, has good electrochemical performance and chiral recognition performance, and reduces detection cost and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688801A_ABST
    Figure CN119688801A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an L-cysteine modified island-shaped cobalt sulfide-cobalt oxide heterogeneous nanosheet array / carbon paper used as an electrochemical chiral sensor electrode material. The invention aims to design an electrochemical chiral sensor of a triangular nanosheet heterojunction array so as to realize recognition and quantitative detection of chiral molecules. The method mainly comprises the following steps: 1, growing a Co-based metal organic framework (Co-MOF) triangular nanosheet array on carbon paper at room temperature; 2, calcining the Co-MOF precursor at a high temperature to prepare a cobalt oxide array / carbon paper material (Co3O4 / CP); 3, preparing a cobalt sulfide-cobalt oxide triangular nanosheet array / carbon paper material (Co3S4-Co3O4 / CP) by a hydrothermal vulcanization method; and 4, assembling L-cysteine on the cobalt sulfide-cobalt oxide triangular nanosheet array / carbon paper material (L-Cys (at) Co3S4-Co3O4 / CP) in a liquid phase manner. The synthesis method has the advantages of simplicity, easiness in operation, low energy consumption and the like. The cobalt sulfide-cobalt oxide heterostructure array with good conductivity and L-cysteine (L-Cys) containing abundant chiral sites have a synergistic effect, so that the electrode obtains satisfactory chiral recognition efficiency (IL / ID = 1.50), the electrode shows high current response to L-tryptophan (L-Trp), the sensitivity is 0.33 A.M <-1 >, and the detection limit is 0.021 M (S / N = 3).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material preparation and electrochemical chiral sensors, and in particular to a method for preparing L-cysteine ​​modified island-shaped cobalt sulfide-cobalt oxide heterogeneous nanosheet array / carbon paper as a chiral electrochemical sensor electrode material. Background Art

[0002] Chirality is an inherent property of nature and is widely present in biological compounds and pharmaceutical substances. Chiral enantiomers have similar optical and physical properties, but their pharmacological and biomedical activities may be different or even contradictory, so they have attracted much attention. Among them, tryptophan (Trp) is an important component of protein synthesis in organisms. L-tryptophan (L-Trp) levels are related to liver diseases. L-Trp is also a precursor of the neurotransmitter serotonin, which plays a role in regulating mental state and improving sleep quality. Insufficient L-Trp levels may lead to diseases such as schizophrenia, Parkinson's disease and Alzheimer's disease. D-Tryptophan (D-Trp) is a non-protein amino acid that cannot be effectively metabolized by living systems and may even produce adverse effects. Due to the high similarity between Trp enantiomers, distinguishing their characteristic signals is a major challenge. Therefore, it is of great significance to develop effective methods to identify and detect Trp enantiomers.

[0003] At present, the methods for chiral recognition and quantitative detection of Trp enantiomers mainly include high performance liquid chromatography, colorimetry and fluorescence spectroscopy. However, these methods are usually costly, time-consuming and require complex sample preparation. Electrochemical technology has attracted extensive attention from researchers due to its advantages of low cost, high sensitivity and rapid quantitative analysis.

[0004] The key to realizing electrochemical chiral detection of enantiomeric molecules lies in the development of electrode materials with excellent conductivity and the construction of chiral interfaces. Metal organic frameworks (MOFs) are widely used as chiral recognition electrode materials due to their adjustable structure, porous framework, and large specific surface area. However, their electrochemical detection performance is limited due to poor conductivity. To solve this problem, one method is to add conductive substances such as metal nanoparticles and carbon materials. Another method is to use MOF derivatives because they have excellent conductivity and can maintain the original morphological characteristics of MOF. However, the accumulation of MOF derivative particles will inevitably affect its detection performance.

[0005] Co-MOF-derived highly oriented Co3O4 nanosheet arrays (NSAs) grown on conductive substrates can effectively prevent material aggregation while providing a direct, stable, and fast electron transfer pathway, making them useful in electrochemical sensing. The internal electric field of the heterostructure can enhance the surface reaction kinetics and possess a fine band structure, thus providing the material with excellent conductivity. In particular, the island heterojunction formed by one component on the surface of another component has a solid structure that exposes more heterointerfaces and increases the number of active sites, thereby facilitating charge transfer and improving the adsorption capacity for other molecules. L-cysteine ​​(L-Cys) is a sulfur-containing chiral molecule that is often used as a chiral selector for enantiomer recognition. It easily forms metal-sulfur bonds with metal nanoparticles and is adsorbed by the island heterojunction to construct a chiral interface.

[0006] In summary, the present invention prepares an L-cysteine ​​modified island cobalt sulfide-cobalt oxide heterogeneous nanosheet array / carbon paper. The cobalt sulfide-cobalt oxide heterostructure on the carbon paper has good electrical conductivity, and L-cysteine ​​has efficient chiral selectivity. The synergistic effect of the two exhibits excellent electrochemical chiral recognition ability, and the array has good application prospects as an electrode material for electrochemical chiral sensors. Summary of the invention

[0007] The purpose of the present invention is to design an electrochemical chiral sensor electrode material of an L-cysteine ​​modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array on carbon paper to improve the electrochemical performance and chiral recognition ability of the electrode material.

[0008] The preparation of an electrochemical chiral sensor electrode material of an L-cysteine-modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array of the present invention is carried out according to the following steps: 1. Room temperature growth of Co-based metal organic framework (Co-MOF) triangular nanosheet arrays on carbon paper The carbon paper was ultrasonically treated in a mixture of 10% nitric acid and sulfuric acid (volume ratio of 3:1) for 1-3 h. After washing and drying, the carbon paper was cut into pieces of 2×3 cm 2 0.5~3 mmol Co(NO3)2·6H2O was dissolved in 20 mL of deionized water, and the pink solution was quickly added to a 0.4 M 2-methylimidazole solution. After stirring for 10 minutes, the activated carbon paper was immersed and allowed to stand at room temperature for 1~6 h. The carbon paper was taken out and thoroughly washed, and dried at 70 °C for 4 h to obtain a Co-based metal organic framework triangular nanosheet array (Co-MOF / CP); 2. Preparation of cobalt oxide array / carbon paper material (Co3O4 / CP) by high temperature calcination of Co-MOF precursor The Co-MOF precursor / CP obtained in step 1 was calcined at 200-750°C for 2 h in air at a heating rate of 3-10°C / min to obtain Co3O4 / CP; 3. Preparation of cobalt sulfide-cobalt oxide triangular nanosheet array / carbon paper material (Co3S4-Co3O4 / CP) by hydrothermal sulfurization Add 60-360 mg of thioacetamide to 60 mL of ethanol, stir for 10 min, and then transfer to a high-pressure reactor. Immerse the Co3O4 / CP obtained in step 2 in the solution and sulfide at 90-180°C for 2-10 h. After cooling to room temperature, wash the obtained product with deionized water several times and dry it to obtain Co3S4-Co3O4 / CP. 4. Liquid-phase assembly of L-cysteine ​​onto cobalt sulfide-cobalt oxide triangular nanosheet arrays / carbon paper material (L-Cys@Co3S4-Co3O4 / CP) Dissolve 2-16 mmol L-cysteine ​​in 50 mL of ethanol / water mixed solution (volume ratio of 1:1), immerse the Co3S4-Co3O4 / CP obtained in step 3 in the solution, and stir at 40 °C for 2-6 h. Wash the product with deionized water several times and dry it to obtain L-Cys@Co3S4-Co3O4 / CP.

[0009] Compared with the existing technology, the present invention has the following beneficial effects: (1) An L-cysteine-modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper prepared by the present invention is used as an electrode material for an electrochemical chiral sensor. The island-shaped heterostructure has a solid structure, exposes more heterogeneous interfaces, increases the number of active sites, and promotes charge transfer, so that it has a strong adsorption capacity for other molecules; (2) The L-cysteine ​​modified island cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper prepared by the present invention is used as an electrochemical chiral sensor electrode material, which fully utilizes the sulfur-containing functional group and chiral characteristics of L-Cys. L-Cys is successfully modified to the heterojunction surface and provides abundant chiral recognition sites, which synergizes with the high conductivity of the cobalt sulfide-cobalt oxide heterojunction, making the chiral electrode have excellent recognition and detection capabilities for Trp. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a microscopic morphology photo of an L-cysteine-modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper; Figure 2 The structure, chemical composition and valence state of an L-cysteine-modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper prepared; Figure 3This is a test of the electrochemical performance of an L-cysteine ​​modified island cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper; Figure 4 This is a test of the chiral recognition and quantitative detection capabilities of an electrochemical chiral sensor of L-cysteine ​​modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper; FIG5 is a scanning image of an L-cysteine ​​modified carbon paper-based island-shaped cobalt sulfide-cobalt oxide heterogeneous nanosheet array material. DETAILED DESCRIPTION

[0011] Specific embodiment 1: A method for preparing an L-cysteine-modified island-shaped cobalt sulfide-cobalt oxide heterogeneous nanosheet array / carbon paper as an electrochemical chiral sensor electrode material, specifically according to the following steps: 1. Room temperature growth of Co-based metal organic framework (Co-MOF) triangular nanosheet arrays on carbon paper The carbon paper was ultrasonically treated in a mixture of 10% nitric acid and sulfuric acid (volume ratio of 3:1) for 1-3 h. After washing and drying, the carbon paper was cut into pieces of 2×3 cm 2 0.5~3 mmol Co(NO3)2·6H2O was dissolved in 20 mL of deionized water, and the pink solution was quickly added to a 0.4 M 2-methylimidazole solution. After stirring for 10 minutes, the activated carbon paper was immersed and allowed to stand at room temperature for 1~6 h. The carbon paper was taken out and thoroughly washed, and dried at 70 °C for 4 h to obtain a Co-based metal organic framework triangular nanosheet array (Co-MOF / CP); 2. Preparation of cobalt oxide array / carbon paper material (Co3O4 / CP) by high temperature calcination of Co-MOF precursor The Co-MOF precursor / CP obtained in step 1 was calcined at 200-750°C for 2 h in air at a heating rate of 3-10°C / min to obtain Co3O4 / CP; 3. Preparation of cobalt sulfide-cobalt oxide triangular nanosheet array / carbon paper material (Co3S4-Co3O4 / CP) by hydrothermal sulfurization Add 60-360 mg of thioacetamide to 60 mL of ethanol, stir for 10 min, and then transfer to a high-pressure reactor. Immerse the Co3O4 / CP obtained in step 2 in the solution and sulfide at 90-180°C for 2-10 h. After cooling to room temperature, wash the obtained product with deionized water several times and dry it to obtain Co3S4-Co3O4 / CP. 4. Liquid-phase assembly of L-cysteine ​​onto cobalt sulfide-cobalt oxide triangular nanosheet arrays / carbon paper material (L-Cys@Co3S4-Co3O4 / CP) Dissolve 2-16 mmol L-cysteine ​​in 50 mL of ethanol / water mixed solution (volume ratio of 1:1), immerse the Co3S4-Co3O4 / CP obtained in step 3 in the solution, and stir at 40 °C for 2-6 h. Wash the product with deionized water several times and dry it to obtain L-Cys@Co3S4-Co3O4 / CP.

[0012] Specific embodiment 2: A method for preparing an L-cysteine ​​modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper as an electrochemical chiral sensor electrode material, specifically according to the following steps: The difference between this embodiment and the first embodiment is that the amount of Co(NO3)2·6H2O in step 1 is 0.5-2 mmol, and the standing time at room temperature is 1-4 h. The rest is the same as the first embodiment.

[0013] Specific embodiment 3: A method for preparing an L-cysteine ​​modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper as an electrochemical chiral sensor electrode material, specifically according to the following steps: The difference between this embodiment and the first and second embodiments is that the carbonization temperature in step 2 is 200-600° C. The rest is the same as the first and second embodiments.

[0014] Specific embodiment 4: A method for preparing an L-cysteine ​​modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper as an electrochemical chiral sensor electrode material, specifically according to the following steps: The difference between this embodiment and the specific embodiments 1 to 3 is that the content of thioacetamide in step 3 is 120-360 mg, the vulcanization temperature is 90-160° C., and the vulcanization time is 2-6 h. The rest is the same as the specific embodiments 1 to 3.

[0015] Specific embodiment 5: A method for preparing an L-cysteine ​​modified island-shaped cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper as an electrochemical chiral sensor electrode material, specifically according to the following steps: The present embodiment is different from the specific embodiments 1 to 4 in that the content of L-cysteine ​​in step 4 is 2 to 12 mmol. The rest is the same as the specific embodiments 1 to 4.

[0016] The following test is used to verify the effect of the present invention: The method for preparing an L-cysteine ​​modified island cobalt sulfide-cobalt oxide heterojunction nanosheet array / carbon paper material used as an electrochemical chiral sensor electrode material in this experiment is specifically carried out in the following steps: 1. Room temperature growth of Co-based metal organic framework (Co-MOF) triangular nanosheet arrays on carbon paper The carbon paper was ultrasonically treated in a mixture of 10% nitric acid and sulfuric acid (volume ratio 3:1) for 2 h. After washing and drying, the carbon paper was cut into pieces of 2 × 3 cm 2 1 mmol Co(NO3)2·6H2O was dissolved in 20 mL of deionized water, and the pink solution was quickly added to a 0.4 M 2-methylimidazole solution. After stirring for 10 minutes, the activated carbon paper was immersed and allowed to stand at room temperature for 3 h. The carbon paper was taken out and thoroughly washed, and dried at 70 °C for 4 h to obtain a Co-based metal organic framework triangular nanosheet array (Co-MOF / CP); 2. Preparation of cobalt oxide array / carbon paper material (Co3O4 / CP) by high temperature calcination of Co-MOF precursor The Co-MOF precursor / CP obtained in step 1 was calcined at 350°C for 2 h in air at a heating rate of 5°C / min to obtain Co3O4 / CP; 3. Preparation of cobalt sulfide-cobalt oxide triangular nanosheet array / carbon paper material (Co3S4-Co3O4 / CP) by hydrothermal sulfurization 240 mg of thioacetamide was added to 60 mL of ethanol, stirred for 10 min, and then transferred to a high-pressure reactor. The Co3O4 / CP obtained in step 2 was immersed in the solution and sulfurized at 130 °C for 4 h. After cooling to room temperature, the obtained product was washed several times with deionized water and dried to obtain Co3S4-Co3O4 / CP. Liquid-phase assembly of L-cysteine ​​onto cobalt sulfide-cobalt oxide triangular nanosheet arrays / carbon paper (L-Cys@Co3S4-Co3O4 / CP) 6 mmol L-cysteine ​​was dissolved in 50 mL of ethanol / water mixed solution (volume ratio of 1:1), the Co3S4-Co3O4 / CP obtained in step 3 was immersed in the solution and stirred at 40 °C for 3 h. The product was washed several times with deionized water and dried to obtain L-Cys@Co3S4-Co3O4 / CP.

[0017] The present invention uses a three-electrode system to test the electrochemical properties of the material, with a platinum wire as a counter electrode, a silver / silver chloride electrode as a reference electrode, and L-Cys@Co3S4-Co3O4 / CP as a working electrode, and electrochemical detection is performed in 0.1 M PBS buffer.

[0018] Figure 1 is the morphology of L-Cys@Co3S4-Co3O4 / CP; Co-MOF triangular nanoarrays with a thickness of 200 nm are evenly distributed on the surface of CP fibers ( Figure 1a, e); During the calcination process, the organic ligands in the Co-MOF precursor are pyrolyzed, Co-MOF is transformed into Co3O4, the thickness of the nanosheets becomes thinner, and the gap between the nanosheets becomes larger ( Figure 1 b, f); the gap between the Co3S4-Co3O4 nanosheets obtained by hydrothermal sulfidation is further enlarged ( Figure 1 c, g); After L-Cys modification, the nanosheets still maintain a triangular morphology, and the thickness of the nanosheets increases ( Figure 1 d, h); The transmission images further show the triangular nanosheet morphology of Co3S4-Co3O4 ( Figure 1 i); The in-situ formed island-shaped Co3S4 is evenly distributed on the Co3O4 nanosheets ( Figure 1 j); High-resolution transmission electron microscopy (HRTEM) image of Co3S4-Co3O4 shows two lattice fringes with spacing of 0.24 and 0.19 nm, corresponding to the (311) crystal plane of Co3O4 and the (422) crystal plane of Co3S4, respectively ( Figure 1 k). The selected area electron diffraction (SAED) pattern clearly shows the polycrystalline diffraction rings of the Co3S4-Co3O4 heterojunction ( Figure 1 l); The energy spectrum results show that Co, S, O, C, and N elements are evenly distributed on the surface of L-Cys@Co3S4-Co3O4 / CP ( Figure 1 m).

[0019] Figure 2 It is the structure, chemical composition and valence diagram of L-Cys@Co3S4-Co3O4; Figure 2 In a, the XRD spectrum of Co3O4 shows obvious peaks at 31.2°, 36.8°, 44.8°, 59.4° and 65.4°, corresponding to (220), (311), (400), (511) and (440) of Co3O4, respectively (standard card JCPDS No. 42-1467); for Co3S4-Co3O4, two gentle peaks appear at 47.3° and 50.6°, corresponding to the (422) and (511) crystal planes of Co3S4, respectively (standard XRD card JCPDS No.19-0367); after L-Cys modification, 5 obvious diffraction peaks appeared at 19.7°, 28.3°, 33.1°, 38.5° and 42.2°, which can well correspond to the (101), (211), (002), (150) and (151) crystal planes of L-Cys (standard card JCPDS No.32-1636); the above results show that part of Co3O4 is in situ converted into Co3S4 after sulfurization, and it also shows that L-Cys is successfully modified onto Co3S4-Co3O4; Figure 2 b is the FTIR spectrum of Co3S4-Co3O4 at 1116 and 614 cm-1 Obvious characteristic peaks were observed at 3440, 3180, 2550 and 1608 cm -1 The peaks at correspond to the characteristic peaks of OH, NH, SH, and CO, respectively. The spectrum of L-Cys@Co3S4-Co3O4 shows a series of characteristic peaks of L-Cys and Co3S4-Co3O4, which further indicates that L-Cys is successfully modified on the surface of Co3S4-Co3O4; in addition, no SH peak of L-Cys is observed in the spectrum of L-Cys@Co3S4-Co3O4; this indicates that SH is involved in the synthesis of L-Cys@Co3S4-Co3O4, which further indicates that L-Cys and Co3S4-Co3O4 nanosheets are connected by metal-sulfur bonds; in the XPS spectrum of L-Cys@Co3S4-Co3O4, characteristic peaks mainly located at Co 2p, O 1s, N 1s, C 1s, and S 2p can be observed ( Figure 2 c); Co 2p has obvious spin-orbit double peaks, and their binding energies are 793.2 and 778.3 eV, corresponding to Co 2p 1 / 2 and Co 2p 3 / 2 The double peaks at 793.2 and 778.3 eV are related to Co 3+ Correspondingly, the double peaks at 797.3 and 781.2 eV are related to Co 2+ The two satellite peaks at 802.4 and 786 eV indicate that Co 2+ The existence of Figure 2 d); 532.8, 531.3 and 530.4 eV in the O 1s spectrum are C-OH, OC=O and metal-oxygen bond (MO) respectively ( Figure 2 e); The peaks of N 1s spectrum at 401.1 and 400.5 eV can be attributed to the characteristic peaks of -NH2 and CN groups ( Figure 2 f); C 1s shows characteristic peaks of C=C, C-OH and -COOH ( Figure 2 g); The S 2p spectrum consists of two peaks at 164.7 and 163.4 eV, belonging to S 2p 1 / 2 and S 2p 3 / 2 state( Figure 2 h).

[0020] Figure 3 The electrochemical performance diagram of L-Cys@Co3S4-Co3O4 / CP. A pair of redox peaks were observed in the CV test. Compared with CP, the redox peak current of Co3O4 / CP increased significantly, and the peak current after in-situ sulfurization was further enhanced. The L-Cys@Co3S4-Co3O4 / CP electrode had the highest oxidation peak current ( Figure 3 a); The redox peak current value increases with the increase of scan rate ( Figure 3 b), is linearly related to the scanning rate, and the corresponding equation is and ( Figure 3 c), indicating that the diffusion process plays a dominant role in the reaction of L-Cys@Co3S4-Co3O4 / CP electrode in L-Trp solution. Figure 3 d is the Nyquist plot of each electrode, which is semicircular in high frequency region and linear in low frequency region. The semicircle diameter of L-Cys@Co3S4-Co3O4 / CP electrode is the smallest, and the value of the semicircle diameter corresponds to the electron transfer resistance (Rct) value in the Randles equivalent circuit. The equivalent circuit is shown in Figure 3 e, where Rs represents the contact resistance with the solution, Zw is the Warburg impedance, and C1 and C2 are the capacitances; through the EIS fitting results, the Rct values ​​of Co3O4 / CP, Co3S4-Co3O4 / CP and L-Cys@Co3S4-Co3O4 / CP electrodes are calculated to be 3.9, 2.6 and 1.5 Ω, respectively. A pair of symmetrical redox peaks can be seen in the electrode in K3Fe(CN)6, and the peak current value increases with the increase of the scan rate ( Figure 3 f), and is linearly related to the scanning rate, and the corresponding equation is: and According to the Randles-Sevcik equation, the electrochemically active surface areas (ECSA) of the L-Cys@Co3S4-Co3O4 / CP electrodes were 4.25 cm 2 Figure 3 h investigated the effect of pH on L-Trp detection and observed that the oxidation peak current moved toward negative potentials as pH increased, reaching a maximum value at pH = 7 ( Figure 3 i), so it is selected as the optimal pH value.

[0021] Figure 4 The results of the chiral recognition and quantitative detection test of the L-Cys@Co3S4-Co3O4 / CP electrode are shown in Figure 2. The oxidation peaks of L-Trp and D-Trp can be seen at a voltage of 0.75 V, and the oxidation peak current of L-Trp is significantly higher than that of D-Trp. The recognition efficiency of the electrode for Trp enantiomers (I L / I D , the current ratio of the electrode in L-Trp and D-Trp solutions) is 1.50 ( Figure 4 a), showing excellent chiral recognition ability. Figure 4 b-4c is the quantitative detection result of the electrode pair L and D-Trp. As the concentration increases, the oxidation peak current gradually increases and shows a good linear relationship with the concentration. The corresponding equation is: ( Figure 4 d); The sensitivity of the electrode to L-Trp and D-Trp is 0.33 µA·µM -1 and 0.24 µA·µM -1 , the limits of detection (LOD) were 0.021 µM and 0.029 µM, respectively (S / N=3); Figure 4 e is the quantitative test result of the electrode on the L-Trp content in the racemic mixture. The oxidation peak current increases with the increase of L-Trp content and shows a good linear relationship with the content. The corresponding equation is: ( Figure 4 f); Figure 4 g is the anti-interference ability test result of the electrode. After adding biological interference molecules (ascorbic acid, dopamine, uric acid, phenylalanine, glutamic acid) to L-Trp and D-Trp solutions, the current response decreased, while the recognition efficiency was almost unaffected, indicating that the electrode has good anti-interference ability. Five electrodes were prepared under the same conditions for testing, and the relative standard deviation (RSD) value of the recognition efficiency was 2.6% ( Figure 4 h), the RSD value of the same electrode after 5 tests was 3.3% ( Figure 4 i), indicating that the L-Cys@Co3S4-Co3O4 / CP electrode has good repeatability and reproducibility.

[0022] FIG5 is an abstract figure, which is a morphology of L-cysteine ​​modified carbon paper-based island-shaped cobalt sulfide-cobalt oxide heterogeneous nanosheet arrays, showing triangular nanosheets uniformly distributed on the carbon paper fibers.

Claims

1. An L-cysteine ​​modified island cobalt sulfide-cobalt oxide heterogeneous nanosheet array / carbon paper, characterized in that A method for preparing L-cysteine ​​modified island cobalt sulfide-cobalt oxide heterogeneous nanosheet array / carbon paper as a chiral electrochemical sensor electrode material is carried out by the following steps:

1. Room temperature growth of Co-based metal organic framework (Co-MOF) triangular nanosheet arrays on carbon paper The carbon paper was ultrasonically treated in a mixture of 10% nitric acid and sulfuric acid (volume ratio of 3:1) for 1-3 h. After washing and drying, the carbon paper was cut into pieces of 2×3 cm 2 0.5~3 mmol Co(NO3)2·6H2O was dissolved in 20 mL of deionized water, and the pink solution was quickly added to a 0.4 M 2-methylimidazole solution. After stirring for 10 minutes, the activated carbon paper was immersed and allowed to stand at room temperature for 1~6 h. The carbon paper was taken out and thoroughly washed, and dried at 70 °C for 4 h to obtain a Co-based metal organic framework triangular nanosheet array (Co-MOF / CP); 2. Preparation of cobalt oxide array / carbon paper material (Co3O4 / CP) by high temperature calcination of Co-MOF precursor The Co-MOF precursor / CP obtained in step 1 was calcined at 200-750°C for 2 h in air at a heating rate of 3-10°C / min to obtain Co3O4 / CP; 3. Preparation of cobalt sulfide-cobalt oxide triangular nanosheet array / carbon paper material (Co3S4-Co3O4 / CP) by hydrothermal sulfurization Add 60-360 mg of thioacetamide to 60 mL of ethanol, stir for 10 min, and then transfer to a high-pressure reactor. Immerse the Co3O4 / CP obtained in step 2 in the solution and sulfide at 90-180°C for 2-10 h. After cooling to room temperature, wash the obtained product with deionized water several times and dry it to obtain Co3S4-Co3O4 / CP.

4. Liquid-phase assembly of L-cysteine ​​onto cobalt sulfide-cobalt oxide triangular nanosheet arrays / carbon paper material (L-Cys@Co3S4-Co3O4 / CP) Dissolve 2-16 mmol L-cysteine ​​in 50 mL of ethanol / water mixed solution (volume ratio of 1:1), immerse the Co3S4-Co3O4 / CP obtained in step 3 in the solution, and stir at 40 °C for 2-6 h. Wash the product with deionized water several times and dry it to obtain L-Cys@Co3S4-Co3O4 / CP.

2. The preparation method according to claim 1, characterized in that In step 1, the amount of Co(NO3)2·6H2O is 0.5~2 mmol, and the standing time at room temperature is 1~4 h.

3. The preparation method according to claim 1, characterized in that: The carbonization temperature in step 2 is 200-600°C.

4. The preparation method according to claim 1, characterized in that In step 3, the content of thioacetamide is 120-360 mg, the vulcanization temperature is 90-160° C., and the vulcanization time is 2-6 h.

5. The preparation method according to claim 1, characterized in that The content of L-cysteine ​​in step 4 is 2-12 mmol.